Effectiveness of Implementation of Good Agricultural Practices and Productivity Improvement Strategy for Arabica Specialty Kintamani Coffee - I Gusti Bagus Udayana; I Gusti Agus Maha Putra Sanjaya; Yohanes Parlindungan Situmeang; I Komang Suwedi (Agriwar Journal, 2023)
Specialty Arabica coffee is coffee beans, roasted coffee, and ground coffee that come from a certain geographical area and have a delicious, unique, and different taste from other coffees. So far, Bali Kintamani Arabica Coffee, which is classified as specialty coffee, grows and develops at altitudes above 1,000 meters above sea level. The study aimed to determine the effectiveness of the application of GAP in increasing the productivity of Kintamani specialty Arabica coffee, to find out what factors influence the strategy for increasing the productivity of Kintamani speciasylty Arabica coffee, and to find out what strategies can be applied to increase the productivity of Kintamani specialty Arabica coffee. This research was conducted in Belantih Village and Catur Village, Kintamani District, Bangli Regency, Bali Province. To analyze the effectiveness of implementing Good Agricultural Practices, researchers used descriptive qualitative analysis to analyze the data obtained from the results of the FGD (Forum Group Discussion) conducted at the research location. The application of GAP turned out to affect increasing the productivity of Kintamani specialty arabica coffee. The results of IFE and EFE analysis on the IE Matrix found that Kintamani specialty Arabica coffee was in a strong position and had opportunities, so 7 strategies were developed, namely collaboration in raw material research, raw material supply chain, and alternative raw materials. procurement, development of product diversification that has Kintamani identity or characteristics through strategic research results, conducting periodic performance appraisals, preparing alternative supply chain strategies for raw materials to distribution, designing farmer group cooperation to secure market prices, developing production operational standards through adjustments and approaches to local culture, developing integrated promotion management. Keywords: Good Agricultural Practices, Strategy, Productivity, Arabica Coffee Specialty, Kintamani